Evaluation of arrow release in highly skilled archers using an acoustic measurement system - Heller, M. (Procedia Engineering, 2012)
During aiming, an archer holds the stretched bow while a small piece of metal - the clicker - presses the arrow lateral against the bow. At the end of the aiming phase, the archer pulls the arrow back until the clicker slips over the arrowhead and causes a click, and then the archer shoots. To investigate the precision of the timing of this motor program, an acoustic measurement system has been developed. The system is composed of a modular microphone (AKG C 480 B comb-ULS/61), and an external FireWire Audio Interface (Focusrite Saffire LE 24Bit / 96 kHz). From the audio signal, the time of the clicker's fall, the release of the shot and the hit of the target can be detected. Seven elite archers (two males, five female) performed 30 shots (ten ends of three arrows without any time limit) at 18 m indoors. Means and coefficients of variation (CV) were calculated from average speed and clicker time, i.e. the time between the click and the release of the shot. Forward stepwise multiple linear regression analysis was done to determine mean scores. CV of the clicker time accounted for 66% of the variability in scoring. A "leave-one-out" cross validation procedure revealed consistent estimate of the model (all corrected R2 were in a range of 0.66 and 0.75 with p<0.03). It has been shown that a highly precise timing in arrow release in terms of small CVs of clicker time is important for high mean scoring.